Unpacking the roles of social media, self awareness, and social influence in shaping perceived value among Generation Z - Nia Septiana; Dean Salomo Anthonino Kumenaung; Faris Faruqi; Hendryadi Hendryadi (Jurnal Riset Manajemen dan Bisnis, 2025)
The environmental impact of fast fashion has increased interest in sustainable alternatives, particularly among Generation Z, a key consumer group for eco-friendly fashion. This study explores how Social Media, Self-awareness, and Social Influence affect the perceived value of sustainable fashion for Generation Z in Indonesia. Using a structured questionnaire with 190 respondents, data were analyzed through Partial Least Squares Structural Equation Modeling (PLS-SEM). Results show that Social Media has the strongest positive influence on Perceived Value, indicating its critical role in shaping evaluations of sustainable fashion. Self-awareness also positively correlates with Perceived Value, suggesting that more self-aware consumers better recognize the benefits of sustainable fashion. Conversely, Social Influence has a positive but non-significant relationship with Perceived Value, indicating that peer influence alone may not adequately shape deeper perceptions without direct experience or detailed product information